A Comparative Study of Students’ Satisfaction towards Service Quality According to Their Demographic sat Angkor Khemera University (Aku) in Kompongspeu Province in Cambodia - Phallip, Yin; Ye, Yan (Scholar: Human Sciences, 2017)
This study was conducted to compare students' satisfaction towards service quality according to their demographics at Angkor Khemera University (AKU) in Kompongspeu Province in Cambodia. The collected data were analyzed by Frequency, Percentage, Mean, Standard Deviation, Independent Samples t-test, and One-Way ANOVA. The result found that there were no significant differences of the students’ satisfaction towards service quality according to their demographics (gender, age and grade level) at AKU in Kompongspeu in Cambodia. In general, the total mean score of students' satisfaction towards service quality of AKU in Cambodia was regarded high. However, the mean score of students' satisfaction towards academic aspect was regarded the highest, while the mean score of students' satisfaction towards group size aspect was regarded the lowest.